Komunikasi Interpersonal Guru dan Murid Anak Berkebutuhan Khusus (ABK) dalam Kegiatan Belajar Mengajar Kelas Inklusif SMA Negeri 1 Gedangan - Yanwar Abi Duha; Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aimed to determine how interpersonal communication between teacher and children with special needs in learning activities inclusive class at senior high school 1 Gedangan. This study used descriptive qualitative method by in-depth interview and observation. Data analysis technique used analytic descriptive method which included collection and composing of data analysis. The result of this study was the teacher in Senior High School 1 Gedangan had done five general quality process into the value of effectiveness interpersonal communication through the way they communicate in the learning process. However, not all of these indicators could be implemented in the type of direct communication. Empathy in the interpersonal communication manifested into the type of giving method in order to facilitate understanding that done by children with special needs. In addition, interpersonal communication through openness process in resolving problem that involve children with special needs and supportiveness through curriculum and method implementation, different implementation between children with special needs and regurel students.